Hvilke konsekvenser har brugersociologien for Den Danske Ordbogs udformning? - Hjorth, Ebba (LexicoNordica, 1994)
Den Danske Ordbog (the Danish Dictionary, DDO) caters for untrained dictionary users, students at all levels, persons with Danish as their second language, and linguists and lexicographers. It is the task of DDO to describe the general language as well as commonly used specialized language, to describe the written language and also include the spoken, to give guidance on the standard language and provide an orthographic norm. Tue article shows how the dictionary considers the needs of its wide target group in the selection of material and the overall arrangement of the dictionary. Tue practice followed by the DDO as regards orthography (alternative spellings, orthographic errors), pronunciation, the language of definitions, its practice as regards citations, and information on valency is shown on the basis of the dictionary skills and the needs of the supposed groups of users.